DAILY WRITING PROGRAM OF ENGLISH DIARY TO IMPROVE THE STUDENTS’ ABILITY TO WRITE - Asti Veto Mortini (Esteem Journal of English Education Study Programme, 2022)
This research was aimed to investigate diary writing activity to improve the students’ writing ability at SMA PGRI 2 Palembang. The question of this study was to determine about, was there any significant difference between the students were taught by using diary writing activity and those were not. This research was conducted in SMA PGRI 2 Palembang, for the second semester 2020-2021 school year. This research could conclude that the diary writing activity to improve the students’ writing ability have a significant impact on students’ writing performance, because based on the result of the test, the students who were taught recount text through writing diary got higher scores than those who were not. From the students’ treatment process, the students in experimental group could improve their writing through diary writing. The average student’s writing performance in experimental group before and after the use of diary writing is significantly improved strategy.